Effects of Curcumin on Iron Overload in Rats - Özbolat, Gülüzar; Alizadeh Yegani, Arash (Sudan Journal of Medical Sciences, 2021)
Background: Iron overload, common in patients with hematological disorders, is a key target in drug development. This study investigated the effects of curcumin on iron overload in rats. Methods: Forty male Wistar rats weighing 139.78 ± 11.95 gm (Mean ± SD) were divided into three equal groups: (i) controls; (ii) iron overload group that received six doses of iron dextran 1000 mg/kg–1 by intraperitoneal injections (i.p.); and (iii) iron overload curcumin group that received six doses of curcumin (1000 mg/kg BW by i.p.). In addition to six doses of iron dextran 1000 mg/kg–1 by i.p., we studied the effects of curcumin on liver function enzymes (alanine aminotransferase [ALT] and aspartate aminotransferase [AST]); antioxidant enzymes (malondialdehyde [MDA], total oxidant status [TOS], total antioxidant status [TAS]); hematological parameters (hemoglobin [Hb], hematocrit [Hct], red blood cells [RBC], white blood cells [WBC], mean corpus volume [MCV], mean corpuscular hemoglobin [MCH], mean corpuscular hemoglobin concentration [MCHC]); and iron parameters (serum iron profile, transferrin, total iron-binding capacity [TIBC], ferritin, and transferrin saturation [TS%]). Results: Curcumin caused a significant decrease in the Hct and Hb concentrations in Group III (P < 0.05). It also significantly reduced the serum levels of ALT (52.45 ± 4.51 vs 89.58 ± 4.65 U/L) and AST (148.03 ± 6.47 vs 265.27 ± 13.02 U/L) at the end of the study (P < 0.05). The TIBC, transferrin levels, and TS significantly decreased when the rats were administered curcumin serum iron (P < 0.05). The TAS level significantly increased in Group III in comparison to Group I (the control group) (P < 0.05). At the end of the study, curcumin significantly reduced the serum levels of TOS (12.03 ± 2.8 vs 16.95 ± 5.05 mmol H2O2/L) while the TAS (1.98 ± 0.42 vs 1.06 ± 0.33 mmol Trolox equiv./L) was increased. Conclusion: The findings of the present study suggest the therapeutic potential of curcumin against iron overload.